Une expertise catholique au service de la pastorale urbaine - Jean-Philippe Warren (Chrétiens et Sociétés, 2015)
In Quebec, sociology, whether religious or not, was in the 1950s directly embedded in pastoral sociology. Finding in a reference to the Chicago School a convenient legitimacy, the French-Canadian pastoral sociology mainly borrowed from the methods of the French Catholic sociology developed by Gabriel Le Bras. However, contrasting social contexts aroused the development of very different works. Thus, we do not find in the analysis of parishes produced in Quebec the thesis that material poverty leads to a progressive distancing of the Church, or that geographical and cultural affiliation has an impact on the variations of the rates of religious practice. In fact, it is always the problem of urbanization as a global phenomenon that orients Quebec sociologists’ research. The collapse of the religious practice in the 1960s only confirmed, at least in appearance, the implacable law of secularization, thereby sounding the death knell on empirical investigations à la Boulard in Canada.